IMPLIKASI RASIO-RASIO KEUANGAN TERHADAP TINGKAT LABA PERUSAHAAN MANUFAKTUR DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Liza Novietta; Ruswan Nurmadi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
The purpose of this study was conducted to analyze the implications of the financial ratios of the rate of profit manufacturing companies partially or simultaneously, as well as analyzing the implications of the size of the company to the financial ratios to improve profit growth in manufacturing companies. This study uses secondary data, ie data manufacturing companies listed in Indonesia Stock Exchange for the years 2010 - 2012. The sample selection is done by purposive sampling and methods of data analysis in this study using multiple linear regression using SPSS version 19.Simultaneous testing provides results of the study with the conclusion that the independent variables, namely DER, ROE, ROA, CR and TATO significant effect on the level of corporate profits. While the partial test, just ROA and TATO that significantly influence the level of corporate profits, while DER, ROE and CR no significant effect on the level of corporate profits. Residual test results on a model of moderation that do conclude that the size of the company is moderating variables that weakened the relationship between the independent variables DER, CR and TATO with the dependent variable level of corporate profits. This is evidenced by the negative coefficient value of each of the independent variables and a significance level above 0.05. While the size of the company does not become a moderating variable that weaken nor strengthen ROE and ROA of independent variables with the dependent variable, namely the level of corporate profits